Conditions of intimate visit penitential benefit, discomforts in prison and perceived stress in psychological welfare in the internal of a criminal establishment of women. - Huanca Lupaca, Lila Norah (2020)
A non-experimental, descriptive-correlational study was carried out with the objective of determining the influence of the prison benefit of the intimate visit on the psychological well-being of the inmates of the Tacna Women's Prison. 96 inmates participated in this investigation, who were selected using the probabilistic sampling procedure. Participating inmates were applied 4 data collection instruments: survey on the benefit of intimate visitation, psychological well-being scale, questioning of discomfort in prison and perceived stress. The results indicate that there is a direct influence on the use of the prison benefit of intimate visits on the psychological well-being of the inmates. This result indicates that the more internal women receive this benefit, the better levels of psychological well-being they can have. Likewise, it was found that 27.5% and 17.5% of the inmates who receive the benefit of the intimate visit are located at the Very high and High levels (respectively) in the Psychological Well-being variable. On the other hand, it was established that 38.5% of the inmates in the sample are located at the Fair level, regarding the inconvenience they experience in prison. Among the main “annoyances” that the inmates experience is the following: noise (51%), overcrowding (72.9%), schedules (66.7%) and pressures (55.2%). Finally, it was found that the inmates who do not receive an intimate visit exceed in the Very High in stress category that the inmates who do receive intimate visits (13.5% and 4.2%, respectively. Likewise, in the High category, the inmates who do not use the penitentiary benefit of intimate visit exceeds those who do (26% and 6.3%, respectively).